Knowledge, Attitudes, and Beliefs About COVID-19 Vaccine Acceptance During Early Rollout in Urban and Rural Communities of Lampung Province - Dwi Aulia Ramdini; Suharmanto; Rano Kurnia Sinuraya; Asep Sukohar; Shela Sandra Kirana; Annisa Tamara Panjaitan (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2025)
The study was conducted at the beginning of the COVID-19 vaccine rollout in Indonesia and aimed to assess the correlation between knowledge, attitudes and beliefs towards the acceptance of the COVID-19 vaccine in the community of Umbul Niti Village, Jati Agung Sub-district, South Lampung. Umbul Niti Village can be used as an illustration of the village community's acceptance of the COVID-19 vaccine, because it is located not far from Bandar Lampung City. This study is an analytical observational study with a cross sectional approach. The instrument used was the Knowledge, Attitude and Practice Questionnaire. A total of 350 respondents, more than half of them (62.85%) had good knowledge of the COVID-19 vaccine, along with 94% of respondents showing a positive attitude towards vaccine acceptance. Based on the acceptance survey or vaccine acceptance by the community in several provinces, 64.8% stated that they accepted, 27.6% “did not know” and 7.6% “refused”. The success of the vaccination program is largely determined by the level of public acceptance in an effort to achieve herd immunity. Based on statistical analysis, it is known that attitudes and beliefs have a significant relationship with the acceptance of the COVID-19 vaccine (p<0.05). The majority of respondents also viewed the COVID-19 vaccine as safe. Overall, the respondents' level of acceptance of the COVID-19 vaccine was good, with attitudes and beliefs playing an important role in influencing vaccine acceptance. These findings can form the basis of risk communication strategies for future vaccination programs.